Legal Certainty in Restorative Justice as Law Enforcement for Criminal Acts in the New Normal Period - Sari, Retno Dewi Pulung; Pratama, I Gusti Agung Ananta (Budapest International Research and Critics University, 2021)
The Covid-19 Pandemic has made the situation of society must change in order to maintain public health. The rules that have been in effect so far, the perpetrators of the criminal act will undergo an investigation by the police and the prosecutor's office before entering the trial process. During the trial process, the police searched for evidence of the suspect's actions until they got all the evidence. The police investigator submission the case to the prosecutor and carry out after the evidence is complete. With the covid-19 pandemic, covid 19 can be transmitted more easily by having close encounters with other suspects in detention centers. For health reasons, there is no transmission. It is necessary to reduce the number of people who enter detention centers. Moreover, for the time being, the Detention Center occupants have a number that exceeds the capacity, so that it is very prone to transmission. While the suspect must act as a deterrent to their actions. It is necessary to protect the human rights of the perpetrator. In the Indonesian legal system that has the principle of presumption of innocence provides legal certainty with the decision of the judge. So that the termination of the prosecution submitted by the prosecutor will make the public feel the legal certainty to be ruled out. This is a matter that wants to be examined to provide understanding for the public about the attorney general's regulation number 15 of 2020 on the termination of prosecution as restorative justice. The research method uses a normative approach by using research on the criminal procedure law, other implementing regulations, and reference books that support the protection of the criminal's human rights during the Covid-19 pandemic.